2010
DOI: 10.1073/pnas.1008818107
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in dystrophin that trigger muscular dystrophy decrease protein stability and lead to cross-β aggregates

Abstract: A deficiency of functional dystrophin protein in muscle cells causes muscular dystrophy (MD). More than 50% of missense mutations that trigger the disease occur in the N-terminal actin binding domain (N-ABD or ABD1). We examined the effect of four diseasecausing mutations-L54R, A168D, A171P, and Y231N-on the structural and biophysical properties of isolated N-ABD. Our results indicate that N-ABD is a monomeric, well-folded α-helical protein in solution, as is evident from its α-helical circular dichroism spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 49 publications
10
93
0
Order By: Relevance
“…Previous studies have demonstrated that several missense mutations in ABD1 of dystrophin cause protein instability in vitro (18,19). Here, we were able to distinguish between a missense mutation associated with DMD (L54R) from one associated with BMD (L172H) by monitoring protein tertiary structure in vitro (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies have demonstrated that several missense mutations in ABD1 of dystrophin cause protein instability in vitro (18,19). Here, we were able to distinguish between a missense mutation associated with DMD (L54R) from one associated with BMD (L172H) by monitoring protein tertiary structure in vitro (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…In vitro biophysical analyses of the full-length proteins instead revealed that each of the mutations rendered dystrophin more insoluble and less stable during thermal denaturation. Missense mutations analyzed in purified ABD1 fragments also exhibited significant aggregation as assessed by thioflavin T fluorescence, Congo red staining, and electron microscopy (19).…”
mentioning
confidence: 99%
“…Mutated dystrophin is expressed in skeletal muscle of cases with missense point mutations, but to date there are very few publications that evaluate potential genotype-phenotype correlations. Previous studies of point mutations within the actin-binding domain of patients with either DMD or BMD phenotypes have concluded that the dystrophin produced is mostly misfolded, rather unstable and prone to aggregation (39,40). We recently showed that a double point mutation in the central rod domain repeat R23 of a DMD patient leads to a substantially lower thermal and chemical stability as well as slower refolding of the mutated protein compared with the wild-type protein (25).…”
Section: Discussionmentioning
confidence: 99%
“…In-frame deletions constitute the majority of the mutations, and it appears that mutations of the N terminus of dystrophin affecting the actin-binding domain 1 (39,40) or the Cys-rich domain (41) are more severe than the others. However, deletions around exons 45-55 are in a large number of cases accompanied by mild skeletal muscle disease but a possibly severe cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants can result in DMD rather than BMD if the variant affects the actin binding domain [2,21] or the β-dystroglycan binding domain of dystrophin [1]. There are other rare cases of in-frame variants resulting in DMD rather than BMD, e.g.…”
Section: Mutational Spectrummentioning
confidence: 99%